Influence of Light Intensity on the Photosynthesis and Phenolic Contents of Mangifera Indica - C. Linatoc, Alona; Idris, Aisha; Abu Bakar, Mohd Fadzelly (Journal of Science and Technology, 2018)
Light is an important environmental factor that have an influence on a plants photosynthesis and production of secondary metabolites like phenolic compounds and flavonoid. Mangifera indica from the family Anacardiaceae is known to have bioactivity due to its phenolic and flavonoid contents. The objective of the study is to determine the influence of light on the photosynthesis and phenolic contents of M. indica. Photosynthesis of the plant was measured using a portable photosynthesis system referred to as LICOR- 6400. Photosynthetic pigments as well as phenolic and flavonoid contents were quantified using a UV-VIS spectrophotometer. The outcome derived from the study shows that sun exposed leaves of the studied plant were having the maximum photosynthesis, saturation and compensation points (P < 0.05). Â Moreover, sun exposed leaves were having higher carotenoid, phenolic and flavonoid contents but lower chlorophyll contents. This leads to a conclusion that sun leaves of M. indica contribute the highest photosynthesis and phenolic contents to the plant.